ANALISIS TANGGUNG JAWAB MURTAHIN (PENERIMA GADAI) DALAM PELAKSANAAN AKAD RAHN EMAS - RINA HUTAGALUNG (PREMISE LAW JURNAL, 2015)
In Islam, mortage is allowed as long as it is in accordance with Al-Qur’an and As-Sunnah. It is possible that everything conventional had a lot of things which can be answered through Sharia principle., such as interest or risk systems commonly practiced in the economy which are contrary to the teaching of islam.The issues discussed in this study were, first, the regulation of the implementation of gold rahn agreement, the second, responsibility of murtahin (mortage recipient) to gold rahn agreement, and the third, the legal protection for murtahin and rahin in gold rahn agreement.If the rahin breeched the agreement, the dispute was settled through deliberation. If this did not work, the dispute would be settled through National Sharia Arbitration Board. This descriptive analytical study was animed to systematically, factually, and accurately illustrate the problems of murtahin’s responsibility in implementing gold rahn agreement. Islamic Sharia mortgage is an alternative financial institution for the community to determine their choices in financing in muamalah Fiqh, the mortgage agreement called rahn is implemehnted through two Sharia transaction agreements, namely, rahn agreement and ijarah agreement. The implementation of gold rahn agreement in the implementation of Sharia mortgage system should be based on Islamic principle. The institution to settle the dispute between the two parties should be stated in every gold rahn agreement in accordance with the regulation of MUI No.26/DSN-MUI/III/2002 abaout gold rahn. Keyword : Rahn, Gold, Mortgage, Sharia. Agreement